IDIOMS TRANSLATION ANALYSIS IN THE DUBBING OF MULAN MOVIE - Dedeh Ariska; Nida Amalia Asikin; Muhammad Aprianto Budie Nugroho (Indonesian EFL Journal, 2022)
The aims of the research are to find out how English idioms are translated into Indonesian in the dubbing versions as well as translation equivalence, and the strategies used when translating the idioms in the movie. The data are collected from the dubbing in the movie entitled Mulan (2020) in order to achieve the research objectives which are dubbing translation how idioms are translated from English into Indonesia. The researcher applied research design of qualitative method by using document analysis. The researcher found 28 idioms in the dialogue of the movie. For the results, and the number of idioms were translated equivalently into idioms (39.29%) and into non-idioms (60.71%). Secondly, the researcher found that there are 3 from 8 types of translation strategies are used to translate idioms they are: translation by more general word (25%), translation by a neutral/less expressive word (7.14%), and translation by paraphrase using a related word. (67.86%). From the result of the research the translator is successfully translating the idioms properly, even though changing the sentence by paraphrasing but it was able to find the suitable synonyms to convey the real meaning of the idioms.Keywords: translation strategies; idiomatic expression; dubbing translation.